ECLIPTA ALBA (BHRINGRAJ): A PROMISING HEPATOPROTECTIVE AND HAIR GROWTH STIMULATING HERB. - KUMARI, ISHA; KAURAV, HEMLATA; CHAUDHARY, GITIKA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Plants are the primary source of food, shelter, and various remedial approaches. They are being in use for treating various kinds of human ailments across the world since the ancient times. One of such important plants is Eclipta alba hassk (Asteraceae) which is commonly known as Bhringraj and false daisy. This plant is known for its extra-ordinary therapeutic properties. It is one of most widely used plant in traditional systems of medicines such as Ayurvedic, Unani, Sidha, homeopathy, Chinese, and folk. Each part of this medicinal plant contains many important phytochemical constituents such as coumestans, triterpenes, flavonoids, steroids, polypeptides, and saponins. It is majorly used for enhancing the growth, strength, and blackening of hair. It is used as the main ingredient in many hair oils. It significantly treats problems related to hair such as hair fall, dandruff, premature greying, and baldness. E. alba exhibits many other important biological properties such as anticancer, anti-bacterial, anti-viral, anti-stress, and immunomodulatory. Thus, this medicinal plant is playing a vital role in the medical field and cosmetic industry. The present review is a summary of phytomedicinal importance of E. alba in Ayurveda as well as folk medicine system.